Survey on energetic short rotation forestry systems – Possibilities of spatial development and job creation - Antal, József; Grasseli, Gábor (Acta Agraria Debreceniensis, 2010)
Both the European and the Hungarian rural areas suffer multi dimensional problems. Beside infrastructural under development the most important difficulty is employment. Unemployment is significant in the rural areas, while other structural characteristics like education, profession, work circumstances and seasonality worsen this unfavourable situation. It can be stated that the challenge with the highest priority in rural and spatialdevelopment is to create jobs and to strengthen local employment. The authors examine the job generating possibilities of energetic biomass of agricultural origin in a structural point of view. The aim is to develop spatial biomass product line models that permanently support the raise of employment by utilizing the possibilities of the European Union support policy and the popularity of this branch.